Implementation of Monte Carlo Simulation to Measure Value at Risk (VaR) in BNI Bank Stock Investments - Isma Muthahharah; Muhammad Fahmudin; Muhammad Nusrang (Program Studi Matematika Universitas Sulawesi Barat, 2026)
This study applies the Value at Risk (VaR) method using Monte Carlo simulation to estimate the maximum potential loss in BNI stock investments. Daily closing prices of BNI stock for 2024 were analyzed to calculate returns and assess risk at confidence levels of 99%, 95%, and 90%. The Monte Carlo simulation, performed with 1,000 iterations, produced estimated maximum losses of approximately 9.7%, 7.4%, and 5.9% of the total investment for the respective confidence levels. These findings demonstrate that a higher confidence level corresponds to a larger potential loss, highlighting the usefulness of VaR combined with Monte Carlo simulation as a tool for evaluating and managing stock investment risk.